Ammonium Ion Requirement for the Cell Cycle of Mycobacterium avium - McCarthy, Charlotte (1978)
Mycobacterium avium has a defined cell cycle in which small cells elongate to about five times their original length and then divide by fragmentation. The nitrogen requirement for production of maximal number of colony-forming units was assessed by varying concentrations and kinds of nitrogen source in the medium. Ferric ammonium citrate at a concentration in 7H10 medium of 0.17 μmol/ml or ammonium chloride at 0.25 μmol/ml as the nitrogen source permitted the cells to elongate and to undergo limited division, with the final culture at 4 × 10(7) colony-forming units per ml. Ammonium chloride at 2.5 μmol/ml or glutamine at 1.37 μmol/ml supported completion of the cell cycle with final colony-forming units at about 5 × 10(8)/ml. Other amino acids, including glutamic acid, at 2.5 μmol/ml did not support completion of the cell cycle, although in most cases an intermediate number of colony-forming units per milliliter were formed. Limited uptake of [(14)C]glutamic acid and uptake of [(14)C]glutamine were not detectable until cell fission began. Cells not limited for nitrogen took up five times as much (35)S during fission as limited cells did during the same time. The nonlimited cells contained 10 times as much sulfolipid as the nitrogen-limited cells at the end of the cell cycle. These results demonstrate that rapidly dividing cells of M. avium utilize amino acids and sulfur and also synthesize sulfolipids in events that are apparently separable from metabolic functions of elongating cells. The results are contrasted with those found for other mycobacteria in which no cell cycle has been demonstrated.